2008
DOI: 10.1074/jbc.m704153200
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Efflux of Amino Acids and Glutathione from Cultured Hippocampal Slices by Omission of Extracellular Calcium

Abstract: Omission of extracellular Ca2؉ for 15 min from the incubation medium of cultured hippocampal slices stimulated the efflux of glutathione, phosphoethanolamine, hypotaurine, and taurine. The efflux was reduced by several blockers of gap junctions, i.e. carbenoxolone, flufenamic acid, and endothelin-1, and by the connexin43 hemichannel blocking peptide Gap26 but was unchanged by the P2X 7 receptor inhibitor oxidized ATP, a pannexin1 hemichannel blocking peptide and an inactive analogue of carbenoxolone. Pretreatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 62 publications
4
52
0
Order By: Relevance
“…Although separated cultures allow us to dissect in detail the A␤ 25-35 -induced hemichannel activity in individual cellular types, the use of acute hippocampal slices was essential to study this response in a more integrated system. Up to now, the presence of functional hemichannels in brain slices (Liu et al, 2006;Rouach et al, 2008;Stridh et al, 2008) was solely observed under extracellular Ca 2ϩ /Mg 2ϩ -free condition, a protocol that promotes hemichannel opening but does not reflect a physiological situation. Here, we show that A␤ [25][26][27][28][29][30][31][32][33][34][35] induces hemichannel activity in hippocampal microglia, astrocytes, and neurons under normal extracellular divalent cationic conditions.…”
Section: A␤-induced Neuronal Death Occurs Through a Sequence Of Hemicmentioning
confidence: 99%
“…Although separated cultures allow us to dissect in detail the A␤ 25-35 -induced hemichannel activity in individual cellular types, the use of acute hippocampal slices was essential to study this response in a more integrated system. Up to now, the presence of functional hemichannels in brain slices (Liu et al, 2006;Rouach et al, 2008;Stridh et al, 2008) was solely observed under extracellular Ca 2ϩ /Mg 2ϩ -free condition, a protocol that promotes hemichannel opening but does not reflect a physiological situation. Here, we show that A␤ [25][26][27][28][29][30][31][32][33][34][35] induces hemichannel activity in hippocampal microglia, astrocytes, and neurons under normal extracellular divalent cationic conditions.…”
Section: A␤-induced Neuronal Death Occurs Through a Sequence Of Hemicmentioning
confidence: 99%
“…4). Connexins and glutamate/aspartate transporters (GLAST) have also been suggested to mediate the efflux of GSH in excitable cells (87,204,224,225) (Table 1 and Fig. 4).…”
Section: Fig 4 Plasma Membrane Gsh Efflux Pumps Distinct Candidatementioning
confidence: 99%
“…13,[15][16][17][18] In this manner, Cx hemichannels could have an influence on the progression of the cell death process as has been documented in HeLa cells transfected with Cx43 exposed to various apoptotic agents 15 and to trigger apoptosis in Marshall and L2 lung epithelial cells in response to oxidative cell stress. 6 In addition, they are the essential transducers of the antiapoptotic effects of bisphosphonates, drugs used in the treatment of bone diseases, and may thus promote cell survival as well.…”
mentioning
confidence: 99%
“…They have been shown to release molecules such as adenosine triphosphate (ATP), glutamate, nicotinamide adenine dinucleotide (NAD þ ), prostaglandins and glutathione. 5,11,16,18,20 These substances may act in a paracrine manner on surrounding cells thereby modulating the spatial spreading of the cell death process. 17 The aim of this study was to investigate the role of both Cx channels in the communication of apoptotic signals to surrounding cells.…”
mentioning
confidence: 99%